Molecular Relatedness of Salmonella enterica Typhimurium Isolates from Feces and an Infected Surgical Wound - Qin, Haiyan (Infect Drug Resist, 2020)
PURPOSE: Salmonella enterica serovar Typhimurium infection is common in foodborne diseases, but its isolation from surgical incisions is rare. Our aim in this study was to trace the transmission source of a surgical incision infected with S. Typhimurium in a Yunnan Province hospital patient and elucidate the underlying molecular mechanisms of antibiotic resistance. METHODS: Primers were designed to amplify the drug-resistance genes using polymerase chain reaction (PCR). Susceptibility to antibiotics was determined using Etest strips. Macrorestriction profiles were analyzed using pulsed-field gel electrophoresis (PFGE) and XbaI. The two isolates were characterized using agglutination tests and multilocus sequence typing (MLST). RESULTS: MLST analysis revealed that S. Typhimurium isolates SM043 and SM080 belonged to the same genotype, ST34, and PFGE revealed that SM043 and SM080 had high similarity. The isolates were both resistant to third-generation cephalosporins. SM043 harbored the antibiotic resistance genes blaCTX-M-15, blaTEM-1, qnrS-1, qnrB, and acc-3, whereas blaCTX-M-15, blaTEM-1, blaCMY-2, qnrS-1, and acc-3 were detected in SM080. CONCLUSION: The surgical incision infection by S. Typhimurium may have been hospital-acquired. Thus, it is critical to strengthen hospital sanitation by addressing hand hygiene and sterilization of the operational environment to avoid outbreaks of nosocomial Salmonella infections.